Peningkatan Keterampilan Adaptasi Pengrajin Joglo di Masa Pandemi dengan Strategi Digital Marketing - Putra, Wahyu Sukestyastama; Taufikkurahman, Taufikkurahman (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2021)
Joglo craftsmen are one of the parties affected by the Covid19 virus. In this service activity, assistance is provided to partners to help survive the pandemic. Mentoring is carried out in the form of online training to improve partners' skills and knowledge. The training provided includes graphic design training, website management training and internet marketing training using Facebook ads. The training process is carried out synchronously and asynchronously. The process of monitoring partner activities in service activities is carried out using the Edpuzzle platform. The results of the analysis of the output of training activities and monitoring of activities carried out can be concluded that the process of transferring knowledge to partners can be carried out even though the activities are carried out online. Synchronous and asynchronous online training needs to be carried out simultaneously to maximize the knowledge transfer process.